A Burst Phase Analysis Technique for High Precision Time Delay Estimation of Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (Asia-Pacific Microwave Conference (APMC), 2011)
In this paper, a novel burst phase analysis technique for high precision time delay estimation of frequency hopping GSM signals is presented. The technique makes use of the increased bandwidth of frequency hopping waveforms and acquires and processes the signals in a coherent way. This way, the actual applicable bandwidth for time delay estimation and localization purposes is increased significantly. In case of E-GSM 900 systems, up to 35 MHz of bandwidth can be used which enables localization of mobile phones in the order of a few meters. The technique is therefore ideally suited for search and rescue applications. The presented method may also be applied to TETRA, DECT, IEEE 802.15.4 (ZigBee) or IEEE 802.15.1 (Bluetooth) signals.
elib2cris::1512001600,goetz2011b
Keywords: GSM; TDOA; Localization; Frequency Hopping

A GSM-Network for Mobile Phone Localization in Disaster Scenarios - Rose, Richard; Meier, Christian; Zorn, Stefan; Götz, Alexander; Weigel, Robert (German Microwave Conference, 2011)
This paper deals with an adjustment and an implementation of a modified GSM-network. This network is necessary to enable the localization of mobile phones, primarily in disaster scenarios. In order to localize a mobile phone it is mandatory, that the phone transmits a signal. As a mobile phone transmits only sporadically without request, it has to be enforced to send a signal to be localized. The enforcing of a transmission is done by means of bringing up an auxiliary GSM-network. The configuration of the GSM-network allows the usage of a special handover procedure with frequency hopping. The implementation of frequency hopping considerably increases the accuracy of applied localization techniques.
elib2cris::1512001600,rose2011

A new Approach on Mobile Phone Localization for Search and Rescue Applications - Zorn, Stefan; Rose, Richard; Götz, Alexander; Weigel, Robert (International conference on indoor positioning and indoor navigation (IPIN), 2010)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the Federal Ministry of Education and Research Germany. Here partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. Future developments in the area of mobile phone detection by field intensity measurements will be addressed in this paper.
elib2cris::1512001600,zorn2010
Keywords: Clocks; GSM; Phase locked loops; Protocols; Radio frequency; Universal Serial Bus

A new System for Mobile Phone Localization for Search and Rescue Applications - Weigel, Robert; Kölpin, Alexander; Rose, Richard; Zorn, Stefan; Götz, Alexander (Future Security, 2011)
elib2cris::1512001600,weigel2011g

A new technique to improve AoA using dual polarization - Rose, Richard; Zorn, Stefan; Götz, Alexander; Fischer, Georg; Weigel, Robert (European Microwave Conference, 2011)
This paper presents a technique for reducing the AoA measurement error caused by the influence of multipath propagation. This technique can be implemented using two approaches, where either the amplitude or the power of the received signals in the polarization domain can be implicated. After the polarization angle of the LOS signal is derived, the dual polarized antenna configuration has to be computationally rotated by this angle to reduce the influence of multipath components. The simulation results show, that the proposed technique leads to a significant reduction of AoA estimation error originated from a multipath component.
elib2cris::1512001600,rose2011a

An ultra wideband positioning system enhanced by a short multipath mitigation technique - Waldmann, Benjamin; Götz, Alexander; Weigel, Robert (Wireless Sensing, Local Positioning, and RFID, 2009. IMWS 2009. IEEE MTT-S International Microwave Workshop on, 2009)
In this paper an approach for high precision local positioning radar using an ultra wideband technique is presented. The concept is based on the standard FMCW (frequency modulated continuous wave) radar principle combined with short pulses to fulfill the emission limits given by the official regulatory authorities. In this way, a high accuracy in dense multipath indoor environments can be achieved, ideally suited for 1D, 2D and 3D localization. A prototype was built which operates at a center frequency of 7.5 GHz utilizing a bandwidth of 1 GHz. With the setup presented in this paper the distance between two wireless units can be measured achieving a standard deviation down to 6 mm. Additionally, we studied the effects of short multipath propagation and present simulation results for an applicable mitigation technique.
elib2cris::1512001600,waldmann2009
Keywords: Ultra Wideband; FMCW; Indoor Positioning; Radar Navigation; Neural Networks; Multipath Channels

A power saving jamming system for E-GSM900 and DCS1800 cellular phone networks for search and rescue applications - Zorn, Stefan; Maser, Matthias; Götz, Alexander; Rose, Richard; Weigel, Robert (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2011)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the German Federal Ministry of Education and Research. In this project partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. To locate a person by his or her mobile phone requires to take over the phone by an own Base Transceiver Station (BTS). Jamming all other networks is one option to achieve that. This paper will introduce a new Field Programmable Gate Array (FPGA) based jamming system which consumes little power and disturbs only small parts of the GSM spectrum but reliably cuts all connections between mobile stations (MS) and existing BTS.
elib2cris::1512001600,zorn2011

A power sensor unit for the localization of GSM mobile phones for search and rescue applications - Zorn, Stefan; Bozsik, Gabor Josef; Rose, Richard; Götz, Alexander; Kölpin, Alexander; Weigel, Robert (IEEE Sensors, 2011)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Recent examples are Haiti 2010 and Fukushima 2011. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces a field strength measurement unit, which is part of the I-LOV project1. In this project partners from relief organizations, universities, and industry investigate enhancements in disaster handling and victim rescue. One possible option is to take advantage of the fact that most people own a mobile phone today and take it with them the whole day. To locate a person by his or her mobile phone requires to find the maximum of its radiated field strength. This paper will show a new power sensor unit for GSM signals. The complete design flow from requirements considerations to measurement results will be demonstrated. A dynamic range of 107 dB is only one of the remarkable outcomes.
elib2cris::1512001600,zorn2011a
Keywords: cellular radio; disasters; earthquakes; geomorphology; mobile handsets; sensor placement; statistical analysis; GSM

A Smart Jamming System for UMTS/WCDMA Cellular Phone Networks for Search and Rescue Applications - Zorn, Stefan; Gardill, Markus; Rose, Richard; Götz, Alexander; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Microwave Symposium Digest (MTT), 2012, 2012)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. This paper introduces one part of the I-LOV project, endorsed by the German Federal Ministry of Education and Research. In this project partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. To locate a person by his or her mobile phone requires to take over the phone by an own Base Transceiver Station (BTS). Jamming all other networks is one option to achieve that. This paper will introduce a new Field Programmable Gate Array (FPGA) based jamming system which disturbs only the absolute necessary parts of the WCDMA spectrum but reliably cuts all connections between mobile stations (MS) and existing BTS. The whole system including the signal generator and the front end will be discussed. Also measurement results will be shown.
elib2cris::1512001600,zorn2012
Keywords: GSM; Jamming; Mobile communication; Mobile handsets; Multiaccess communication; Radio frequency; Spread spectrum communication; FPGA

A Time Difference of Arrival System Architecture for GSM Mobile Phone Localization in Search and Rescue Scenarios - Götz, Alexander; Zorn, Stefan; Rose, Richard; Fischer, Georg; Weigel, Robert (Workshop on Positioning, Navigation and Communication (WPNC), 2011)
In this work, a novel architecture of a time difference of arrival based localization system for GSM mobile phones is proposed. The system is well-suited for search and rescue scenarios and comprises receiving stations for GSM signals, a dedicated GSM base station and a radio frequency jamming system for GSM and UMTS signals. The system may be operated in the E-GSM 900 band providing high penetration of the covering debris material and a sufficient overall bandwidth for the time difference of arrival measurements. In this case, the best attainable accuracy of localization is shown to be in the scale of 5 m. The components of the system are described in more detail and possible implementations are proposed. The system may also be applied for the localization of UMTS mobile phones making use of the integrated GSM functionality. The proposed system represents a novel approach for time difference of arrival based localization of mobile phones in search and rescue scenarios.
elib2cris::1512001600,goetz2011
Keywords: GSM; Localization; TDOA

A Wideband Crosscorrelation Technique for High Precision Time Delay Estimation of Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (European Microwave Conference (EuMC), 2011)
In this paper, a novel wideband crosscorrelation technique for high precision time delay estimation of frequency hopping GSM signals is presented. The technique makes use of the increased bandwidth of frequency hopping waveforms and acquires and processes the signals in a coherent way. This way, the actual applicable bandwidth for time delay estimation and localization purposes is increased significantly. In case of E-GSM 900 systems, up to 35 MHz of bandwidth can be used which enables localization of mobile phones in the order of a few meters. The technique is therefore ideally suited for search and rescue applications. The presented method may also be applied to TETRA, DECT, IEEE 802.15.4 (ZigBee) or IEEE 802.15.1 (Bluetooth) signals.
elib2cris::1512001600,goetz2011a
Keywords: GSM; TDOA; Localization; Frequency Hopping

Coherent Time Difference of Arrival Estimation Techniques for Frequence Hopping GSM Mobile Radio Signals - Götz, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)

Detektionsalgorithmik und Mehrwegekompensationsverfahren für Local-Positioning-Radar-Systeme - Götz, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)
elib2cris::1512001600,goetz2008

GSM Mobile Phone Localization using Time Difference of Arrival and Angle of Arrival Estimation - Zimmermann, Lars; Götz, Alexander; Fischer, Georg; Weigel, Robert (9th International Multi-Conference on Systems, Signals and Devices (SSD), 2012)
The localization methods time difference of arrival (TDOA) and angle of arrival (AOA) are investigated in their capability of high-resolution detection of GSM signals. Because GSM is of narrowband nature, a bandwidth expansion technique that significantly increases the resolution of TDOA is introduced. The algorithms maximum likelihood estimator (for TDOA), root multiple signal classification and estimation of signal parameters via rotational invariance techniques (for AOA) are proposed as a reference for each method. Simulations conducted with noisy signals and multipath propagation demonstrate the potential of TDOA for GSM localization, especially for search and rescue applications. AOA on the other hand is very sensitive to multipath, and is therefore only recommended for open space scenarios.
elib2cris::1512001600,zimmermann2012a
Keywords: cellular radio; direction-of-arrival estimation; mobile handsets; parameter estimation; radiowave propagation; signal classification; AOA; GSM mobile phone localization

Mehrwegekompensationsverfahren für Local-Positioning-Radar-Systeme - Neurale Netze und Ausgleichskurven zur Kompensation kurzer Mehrwegeverzerrungen. - Götz, Alexander; Weigel, Robert; Waldmann, Benjamin (RadioTecC - Radio Techniques and Technologies for Commercial Communication and Sensing Applications, 2008)
elib2cris::1512001600,goetz2008a

Mehrwegekompensationsverfahren zur robusten Entfernungs- und Positionsbestimmung - Götz, Alexander; Waldmann, Benjamin; Weigel, Robert (HF-Report, 2009)
elib2cris::1512001600,goetz2009

Ortung verschütteter Personen anhand ihrer GSM-Mobiltelefone - Rose, Richard; Zorn, Stefan; Götz, Alexander; Weigel, Robert (RadioTecC - Radio Techniques and Technologies for Commercial Communication and Sensing Applications, 2009)
elib2cris::1512001600,rose2009

Ortung von GSM-Mobiltelefonen in Katastrophenszenarien - Götz, Alexander; Rose, Richard; Zorn, Stefan; Weigel, Robert (DGON Navigationskonvent, 2009)
elib2cris::1512001600,goetz2009b

Ortung von GSM Mobiltelefonen zur Vermissten- und Verschuettetensuche - Weigel, Robert; Fischer, Georg; Zorn, Stefan; Rose, Richard; Götz, Alexander (Electrical and Electronic Engineering for Communication Workshop - Entwicklerforum - Fachmesse, 2011)
elib2cris::1512001600,weigel2011c

Performance Analysis of Time Difference of Arrival and Angle of Arrival Estimation Methods for GSM Mobile Phone Localization - Zimmermann, Lars; Götz, Alexander; Fischer, Georg; Weigel, Robert (Communication, Signal Processing & Information Technology, 2017)
The localization methods time difference of arrival (TDOA) and angle of arrival (AOA) are investigated in their capability of high-resolution detection of GSM signals. Because GSM is of narrowband nature, a bandwidth expansion technique that significantly increases the resolution of TDOA is introduced. The algorithms maximum likelihood estimator (for TDOA), root multiple signal classification and estimation of signal parameters via rotational invariance techniques (for AOA) are proposed as a reference for each method. Simulations conducted with noisy signals and multipath propagation demonstrate the potential of TDOA for GSM localization, especially for search and rescue applications. AOA on the other hand is very sensitive to multipath, and is therefore only recommended for open space scenario
Keywords: Time difference of arrival estimation; Direction of arrival estimation; GSM; Maximum likelihood estimation; Multiple signal classification; Estimation of signal parameters via rotational invariance techniques

Performance of Coherent Time Delay Estimation Techniques for Frequency Hopping GSM Signals - Götz, Alexander; Rose, Richard; Zorn, Stefan; Fischer, Georg; Weigel, Robert (Topical Conference on Wireless Sensors and Sensor Networks (RWW / WiSNet), 2012)
In this paper, the performance of coherent time delay estimation techniques for frequency hopping GSM signals is investigated. It is demonstrated that the techniques enable the usage of a substantially higher bandwidth for time delay estimation and localization purposes compared to state-of-the-art techniques. Since resolution and noise performance directly depend on the applied bandwidth of the signals, major improvements can be realized. For E-GSM 900 systems, an overall bandwidth of up to 35 MHz may be used which enables time delay estimation and localization in the scale of a few meters. The coherent time delay estimation techniques are therefore ideally suited for search and rescue applications.
elib2cris::1512001600,goetz2012
Keywords: GSM; TDOA; Localization; Frequency Hopping

Short Multipath Mitigation Technique Using Feedforward Neural Networks - Götz, Alexander; Waldmann, Benjamin; Weigel, Robert (German Microwave Conference (Gemic), 2009)
In this paper a novel approach for mitigation of short multipath distortions is presented. The technique is applicable to FMCW-based distance measurement systems assuming distinctly separated targets. The effects of spectral distortion caused by short multipath propagation in conjunction with Fourier-based frequency analysis methods are mitigated. For this purpose the distorted spectrum is first analyzed and specific characteristics are calculated. A Feedforward Neural Network processes these characteristics and provides a correction frequency relative to the erroneously shifted maximum in order to estimate the true line-of-sight frequency. A comprehensive analysis was performed by means of a two tone test. Applicability to real world environments was investigated by means of a multi tone test using an IEEE 802.15.4a channel model.
elib2cris::1512001600,goetz2009a
Keywords: Cause effect analysis; Distance measurement; Feedforward neural networks; Frequency estimation; Neural networks